Structural, optical and photoconductivity studies of ZnO bicones synthesized by seed-mediated method. (October 2019) - Rajkumar, C.
Abstract: ZnO bicones (BC) have been synthesized by a seed-mediated method using polyethylene glycol (PEG) and triethylamine (TEA). As-synthesized ZnO BC has been characterized by X-ray diffraction method (XRD), UV–visible absorption spectroscopy, Photoluminescence spectroscopy (PL), Fourier Transform Infrared (FTIR) spectroscopy, Scanning Electron Microscopy (SEM), Transmission Electron Microscopy (TEM) and Time-dependent Photoconductivity study. XRD pattern of ZnO BC shows hexagonal wurtzite phase structure. The UV–visible absorption spectrum of ZnO BC shows two absorption band edges at 302 nm and 370 nm due to its diameter and length. The PL spectrum of ZnO BC shows rich zinc interstitial defects due to the presence of an intense peak at 423 nm. The FTIR spectrum of ZnO BC confirms the presence of TEA and PEG. SEM and TEM images of ZnO nanostructures confirm the bicones structure as well as the size of the ZnO BC. Photoconductivity study shows that the time-dependent rise and decay curves of ZnO BC has very high photosensitivity in vacuum medium compared to its air medium due to the presence of hydrocarbon functional groups and oxygen deficiency atmosphere. Highlights: ZnO bicones have been synthesized by the seed mediated method with the help of ZnO seed, triethylamine, and polyethylene glycol. Optical and structural studies have been done for as-synthesized ZnO bicones. Morphological studies have been done for as-synthesized ZnO bicones. Time-dependent photoconductivity studies have been done in air and vacuum media. Photoconductivity of the prepared ZnO bicones has been investigated having a direction of applied field normal to direction of illumination.